Physico-Chemical Characteristics of Giant Featherback (Chitala lopis) and Mackerel (Scomberomorus commerson) Bone Gelatins and Their Potential as Gelling agents in Gel Mixtures for Roselle (Hibiscus sabdariffa L.) Soft Jelly Candies - YULIANI, Yuliani; AGUNG, Bambang Tri; MARWATI, Marwati; CANDRA, Krishna Purnawan (Walailak Journal of Science and Technology (WJST), 2020)
The gel strength of gelatin depends on its raw material. Fish gelatin shows a broad range of gel strengths. Giant featherback and mackerel bone gelatins have the gel strengths 220 and 38 Bloom, respectively. Here, we prepared roselle soft jelly candy using the single gelatin and mixtures gelatins from bovine, giant featherback, and mackerel sources. Roselle calyces extract has been used as a food additive to improve taste, aroma, and antioxidant content. The soft jelly candies (1.5 % w/v roselle extract and 12 % gelling agent) were prepared using three types of gelatin (giant featherback (GF), mackerel (M), and bovine (B)) in four mixtures (GF:B = 1:3, GF:B = 1:1, M:B = 1:3, and M:B = 1:1). This experiment was arranged in a completely randomized design with three replications for each treatment. Physico-chemical and sensory characteristics of the jelly candies were determined. The data were analyzed by ANOVA continued by the LSD test. The results showed that water content, pH, gel strength, hardness, rigidity, and hedonic quality (taste, color, texture, and overall performance) of the roselle soft jelly candies were affected by choice of gelatin, but not total reducing sugar. Roselle soft jelly candy made with giant featherback and bovine gelatin (1:3) mix was the most preferred by the panelists.